(untitled) (Research, Society and Development, 2022)
The aim of this theoretical reflection is to discuss how distance education (DE) has been implemented as a methodology capable of enabling the maintenance of teaching and learning processes due to the COVID-19 pandemic from the year 2020, having as reference the undergraduate courses in nursing. In this reflection, the strengths and weaknesses of distance learning when used as a substitute model for on-site teaching are presented. Therefore, the concept of DE was reflected on, its use in professional training in nursing, the disputes around this use and, finally, a critical reflection based on the literature and on the authors’ experiences as teaching professors of disciplines was presented. in “off-site” format in response to the COVID-19 pandemic. Discussions regarding this problem proved to be theoretically relevant and made it possible to list and reflect the materialities and performances produced in the student and teacher experiences during the pandemic period.